Gendered exclusion and contestation: Malawian women’s migration and work in colonial Harare, Zimbabwe, 1930s to 1963 - Mudeka, Ireen (University of Wisconsin Press, 2021)
States, industrialists and African authorities in colonial southern Africa generally perceived migrant work in masculine terms—especially inter-territorial mobility, the complexities of which fueled the assumption that inter-colonial migration was predominantly undertaken by men. The biases of colonial actors, in turn, brought about later scholars’ obliviousness to women’s experiences, leading them to perpetuate representations of migrant work as a male phenomenon. This article challenges this masculinist understanding of migrant work by focusing on Malawian women’s migration and work in colonial Harare between the 1930s and 1963. It particularly highlights the complexities of these migrations, examining women’s encounters with different territorial regimes, gendered legislation, and transnational controls stretching from Malawi to Zimbabwe. It argues that the colonial states of Malawi and Zimbabwe, urban authorities, and Zimbabwean employers all joined together to exclude women from the legal migrant work stream. However, Malawian women defied the conventional notion of women as sedentary dependents of migrant husbands by migrating to Harare. In Harare, they further contested their exclusion by undertaking various forms of work for survival. This article traces these women’s experiences through discourse analysis of colonial records and oral accounts of two generations of Malawian women and men.